Delayed Surgical Management of a Giant Rhabdomyomatous Meningioma: A Case Report - Iran Chanideh; Masoud Ghadiri; Seyed Hamid Madani; Ali Shoghi; Sasan Alaghemand; Tahereh Mohammadi Majd; Saeed Gharooee Ahangar (Iranian Journal of Neurosurgery)
Background and Importance: Rhomboid meningioma (RM) is one of the rare and aggressive types of meningioma, typically classified as a central nervous system grade III anaplastic meningioma by WHO. In this report, we present an unusual case of RM. Case Presentation: The patient was a 67-year-old man, living in Kermanshah City, Iran. He came to a neurosurgery clinic with a chief complaint of a huge and unusual mass on his skull. Following the brain computed tomography scan and magnetic resonance imaging, the diagnosis of meningioma was considered. The patient underwent surgical intervention for the excision of the mass. Immunohistochemical findings demonstrated the diagnosis of RM (WHO grade III). Conclusion:  RM is a rare and aggressive subtype of meningiomas with a high growth rate and poor prognosis. Early diagnosis and treatment especially in invasive ones can prevent many unpleasant and critical complications; although tumor location has a pivotal role in determining treatment strategy.